Delivering Trichoderma spp spores via seed coating and storage stability at 20 and 25C - Swaminathan, J.; Wilson, M.J.; Jackson, T.A. (New Zealand Plant Protection, 2014)
Trichoderma species have been reported to augment seedling establishment and provide protection from soil borne diseases Many Trichoderma products are simply mixed into soil or compost but seed treatment offers the potential to reduce spore application rates by directly targeting the developing rhizosphere where efficacy is realised This study evaluated the ability of five formulations based on oils and/or biocompatible polymers to adhere Trichoderma spores to wheat seeds and maintain in their initial loading (colony forming units) moisture content () water activity (aw) and spore germination () Spore loading ranged from 22105 20107 spores/seed with the xanthan gumbased biopolymer formulation providing the highest loading Best survival (43 of initial loading) after 3 months of storage at 20C was recorded in the biopolymerbased formulation followed by the polyvinyl pyrrolidone formulation (24) The remaining three formulations had